Genetic Diversity and Prevalence of Porcine Circovirus Type 2 in China During 2000-2019 - Li, Ning; Liu, Jing; Qi, Jiali; Hao, Feng; Xu, Lei; Guo, Kangkang (Frontiers in Veterinary Science, 2021)
As the major pathogen for porcine circovirus-associated disease (PCVAD), porcine circovirus type 2 (PCV2) is no longer treated as an emerging virus anymore. The wide distribution of PCV2 infection in China causes huge economic losses in the swine industry. Currently, it is generally believed that PCV2 has eight genotypes (PCV2a to PCV2h), with PCV2a, PCV2b and PCV2d being widely distributed. To comprehensively explore the genetic diversity and prevalence of PCV2 in China, PCV-2 sequences submitted from China in the GenBank database were retrieved. With a total of 714 PCV2 strains were retrieved, we found that early-submitted PCV2 sequences were mainly collected from coastal provinces in the southeast part of China, which may indicate PCV2 was initially circulating in those regions. From 2002 to 2008, PCV2b was the dominant prevalent genotype in those retrieved sequences. From 2009, PCV2d became the dominant genotype in those sequences, dropping a hint that a potential shift of PCV2b to PCV2d might occur in 2009, which is similar to the patterns at the global level. In addition to the PCV2a, PCV2b, and PCV2d genotypes, novel strains were also characterized. We further revealed that the amino acid sequences consistency of PCV2a Cap is higher than those in other genotypes. Together, this study provided clues for the possible prevalent genotypes and dynamics of genetic diversity in China from 2000 to 2019.